Optimalisasi Peran Tiktok sebagai Peluang Ekonomi Baru bagi Gen Z di Era Digital - Jordy Risky Pratama Hasibuan; Fitria Auldri Desiana (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2025)
TikTok is a social media platform predominantly used by Gen Z, who create short videos. TikTok is not only a medium for entertainment but also creates new economic opportunities. This article aims to explore TikTok's role as a new economic opportunity for Gen Z and to determine the level of knowledge of the younger generation in innovating through TikTok. The methodology used is an exploratory qualitative approach with interview techniques with several narasumberts, with several students from Nahdlatul Ulama University as narasumberts. This study provides knowledge about TikTok as a positive medium in increasing economic opportunities for the younger generation through their creativity. In addition, this study examines the positive impact that TikTok has poured on Generation Z and the future, as well as its implications for increasing independence through digital technology. The results obtained from the interviews indicate that Generation Z has not yet optimized TikTok as a medium for economic opportunities, only limited to entertainment. However, they certainly hope to be able to optimize TikTok in the future through their creativity and innovation.